MANAGEMENT OF OSTEOARTHRITIS BY MATRA VASTI WITH NIMBAMRATAPATOLADI GHRITA- A CASE REPORT - Azeem, Ahmad; Sarika, *Singh (International Journal of Ayurveda and Pharma Research, 2016)
The ability of work of every individual is depends upon the ability of using his joints. Sandhigata vata is one such clinical entity among Vatavyadhis which affects the locomotion of senior citizens of this world in which Dhatukshaya is prime factor which is characterized by certain symptoms like joint stiffness, joint pain, swelling and difficulty of joint movement etc. In Ashtanga Hrudaya, Snehana is mentioned as one of the main treatments of Sandhigata vata. Moreover in Asthidhatugata vata, Bahya-abhyantara sneha is mentioned as treatment and Vastikarma occupies important place in treating Vatavyadhis. An observational study of 15 days in a sample of 15 cases was conducted. Diagnosed cases of Osteoarthritis (Sandhigata Vata) were selected for study from the outpatient unit of Aligarh Unani & Ayurvedic Medical College and ACN Hospital, Aligarh. Patients were selected at random irrespective of age, sex, Prakriti (constitution), Doshic (local humoral) and the joint involvement. Patients subjected to prior Deepana and Pachana procedures internally. It was followed by Matrabasti in with Nimbamratapatoladi Ghrita with constant dose of 60 ml till Vyadhishamana or maximum 2 weeks. Assessment was done before and after study and using structured proforma. Result and Conclusion: Out of 15 patients from 3 patients (20%) has shown complete remission, 6 patients (40%) have shown marked improvement. In 4 patients (26.66%) moderate improvement was found and 2 patients (13.34%) showed mild improvement. No patient remains unimproved.